Tweeting the News: Criminal Justice Agencies and their Use of Social Networking Sites - McGovern, Alyce (2011)
In recent times we have seen an increase in the willingness of criminal justice agencies to engage with new media technologies and social networking sites, not only as a tool for the investigation of criminal activity, but also as a new way of communicating with the public. Sites such as Twitter, YouTube and Facebook are experiencing a growth in their use as communication tools for criminal justice agencies. What is interesting, however, is that different criminal justice agencies are employing these sites in very diverse ways and with distinctive agendas. This paper aims to explore some of the ways in which local and international criminal justice agencies are engaging with new media technologies and social networking sites.Sydney Institute of Criminology; School of Social Sciences at the University of Western Sydne